(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In the article, the development of "green economy" takes a leading place in ensuring sustainable economic development in our country, rational use of limited, nonrenewable economic resources, and increasing energy efficiency. In 2019-2030, the strategy of the transition to the "green economy" of the Republic of Uzbekistan envisages solving the tasks of increasing the energy efficiency of the economy and rational use of natural resources in the conditions of limited, non-renewable economic resources.